2003
DOI: 10.1093/bja/aeg125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on clinical course, C-reactive protein, S100B protein and von Willebrand factor antigen after paediatric cardiac surgery

Abstract: Administration of dexamethasone before cardiopulmonary bypass for paediatric cardiac surgery decreased the inflammatory response, but did not affect the immediate features after surgery or changes in vWf:Ag or S100B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…Several studies have shown that, whereas corticosteroids can reduce levels of certain inflammatory markers, this effect is not universal, and other markers of inflammation may not be impacted. 2,19 In addition, consistent with our previous analysis of a larger cohort of patients, we found that methylprednisolone was associated with increased postoperative infection. 6 This effect was seen only in the lower-risk surgical group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have shown that, whereas corticosteroids can reduce levels of certain inflammatory markers, this effect is not universal, and other markers of inflammation may not be impacted. 2,19 In addition, consistent with our previous analysis of a larger cohort of patients, we found that methylprednisolone was associated with increased postoperative infection. 6 This effect was seen only in the lower-risk surgical group.…”
Section: Discussionsupporting
confidence: 91%
“…1 Although previous studies have shown that corticosteroids are effective at reducing levels of various inflammatory markers in this setting, clinical outcomes associated with corticosteroids are less clear. 2,3 Some analyses have suggested that corticosteroids are associated with improved outcomes, however other recent analyses have called this into question. [4][5][6] Many studies have been limited by small sample size and the grouping of various steroid regimens together in analysis.…”
mentioning
confidence: 99%
“…However, results obtained in double-blind trials with children (36,37) and in adult cohorts (43) could not demonstrate obvious clinical benefits regarding postoperative clinical course, intubation time, stay on ICU, duration of hospitalization, as well as complications including pleural -or pericardial effusions or drainage volume. Anti-inflammatory effects of MP may be clinically beneficial in more complex lesions with longer CPB runs and exaggerated systemic inflammatory response as shown for adults (46).…”
Section: Influence Of Mp On Postoperative Clinical Coursementioning
confidence: 93%
“…Some studies found that steroids can blunt inflammation [7][8][9][10][11][12][13][14] while others found the opposite [15]. Most importantly, it is unclear to what degree this presumed Banti-inflammatoryê ffect also translates into better clinical outcomes [7,10,13]. Firstly, it is very difficult to characterise the multifaceted nature of the SIRS response whereby a variety of cytokines are activated and interact in a rather complex, unpredictable manner [16].…”
Section: Less Inflammation Better Clinical Outcomes?mentioning
confidence: 99%